Transformasi Sumber Daya Manusia dalam Era Industri 5.0: Tantangan dan Peluang Pengembangan Karyawan - Juli Anggraini; Nabila Kintan Oktadinna; Martini Martini (Journal Of Business, Finance, and Economics (JBFE), 2025)
The transformation of human resources (HR) is a crucial aspect in facing the Industry 5.0 era which emphasizes collaboration between humans and smart technology. This research aims to identify the main challenges, analyze opportunities, and evaluate HR development strategies in the context of human-centered innovation. Using a descriptive qualitative approach, data was collected through in-depth interviews with HR managers and employees of companies that are undergoing or have undergone digital transformation, as well as documentation studies of HR policies and roadmaps. The slot deposit 5000 results of the study revealed five main challenges: digital competency gap, resistance to change, limitations of technology infrastructure, lack of managerial support, and high workload during the transformation process. On the other hand, more adaptive human resource development strategies have emerged, such as technology-based training, strengthening digital organizational culture, and implementing hybrid work systems. This study concludes that the success of HR transformation is highly dependent on the synergy between technology, organizational readiness, and inclusive leadership. These findings are expected to make a theoretical contribution to the development of human resource studies as well as practical recommendations for organizations in designing sustainable transformation p